Interaction of human polymorphonuclear leukocytes with Pseudomonas pseudomallei - Razak, Nyonya; Ismail, Ghazally (Microbiology Research Foundation, 1982)
The interaction of Pseudomonas pseudomallei with human polymorphonuclear leukocytes (PMNs) has been eamined. Human PMNs ingested P. pseudomallei after incubation for 60min in the presence of normal serum. The bacteria were however relatively resistant to phagocytosis by human PMNs in the absence of serum or in the presence of heat-inactivated serum (56° for 30min). Rapid intracellular killing of P. pseudomallei was observed in the presence of 10% normal human serum; but killing efficiency was reduced in the presence of heat-inactivated serum. Killing in the leukocyte bactericidal assay was shown to be predominantly due to the PMN bactericidal effect; not to the 10% normal serum contained in the incubation mixture. Ingestion of the bacteria was accompanied by a 2-fold stimulation of the hexose monophosphate pathway (HMP). In the absence of phagocytosis, however, the bacteria failed to show a marked enhancement in the HMP-shunt activity. Electron microscopic evidence showed that degranulation and bacterial morphologic changes occurred within 1hr after the organism was ingested. Our data suggest that human PMNs kill P. pseudomallei efficiently after ingestion of the organism in the presence of thermolabile serum opsonins. The occasional chronic nature of the disease caused by P. pseudomallei, therefore, could not be explained simply by the ability of the organism to survive within PMNs.